How COVID‐19 has impacted immunisation service delivery in Australia: a national study - Michelle L. Giles; Jessica O'Bryan; Margaret Angliss; Sue Lee; Sushena Krishnaswamy (Elsevier, 2022)
Abstract Objective: The objective of this study was to determine the impact the COVID‐19 pandemic had on the delivery of adult, maternal and childhood immunisation services in Australia in 2020 prior to the rollout of COVID‐19 vaccines, and to understand the adaptations made at a service delivery level that may have contributed to the successful delivery of immunisation services during the first year of the pandemic. Methods: An electronic survey was sent to immunisation providers and pharmacists in all states and territories in Australia between November 2020 and December 2020. It explored interruption to the delivery of immunisation services, strategies implemented to maintain services, prioritisation of populations, and self‐reported challenges and solutions initiated by providers. Results: A total of 850 people responded to the survey. Of these, the most common professional groups identified were pharmacists followed by nurse immunisers, nurses/midwives and general practitioners. Several changes were implemented including relocation of vaccination clinics, change to bookings rather than walk‐in appointments, infection prevention measures, clients waiting in cars pre‐ and post‐vaccination and reduced observation period post‐vaccination. Conclusion: The pandemic has provided opportunities for services to trial new and innovative strategies such as electronic pre‐assessment, electronic consent and drive‐through vaccination services. Implications for public health: Immunisation providers mostly viewed these changes positively and intend to continue many post‐pandemic. The experience gained from the trialling of these strategies may be adapted for vaccine delivery and National Immunisation Program vaccines beyond the pandemic.